Effects of mold geometry on fiber orientation of powder injection molded metal matrix composites - Ahmad, F. (American Institute of Physics Inc., 2015)
Fiber orientations in metal matrix composites have significant effect on improving tensile properties. Control of fiber orientations in metal injection molded metal composites is a difficult task. In this study, two mold cavities of dimensions 6x6x90 mm and 10x20x180 mm were used for comparison of fiber orientation in injection molded metal composites test parts. In both mold cavities, convergent and divergent flows were developed by modifying the sprue dimensions. Scanning electron microscope (SEM) was used to examine the fiber orientations within the test samples. The results showed highly aligned fiber in injection molded test bars developed from the convergent melt flow. Random orientation of fibers was noted in the composites test bars produced from divergent melt flow. Â© 2015 AIP Publishing LLC.